Knowledge and communication about the menstrual cycle among rhythmic gymnasts, ballerinas, and dancers - Schulz, M.; Bø, K.; Gram, M. C. D. (International Journal of Environmental Research and Public Health, 2025)
While moderate exercise supports regular menstrual cycle (MC) function, many female athletes experience MC symptoms that negatively influence their training and performance. Hereby, knowledge and communication about this topic are important to promote an athlete`s health and wellbeing. Hence, this study aimed to assess the knowledge and communication surrounding the MC among Norwegian rhythmic gymnasts, ballerinas, and dancers. In total, 116 rhythmic gymnasts, ballerinas, and dancers aged = 16 years training = 3 days per week completed an electronic questionnaire. Of these, 63% (n = 73) reported a lack of knowledge about the MC`s influence on physical fitness and performance, and 39% (n = 45) rated their coaches` or pedagogues` knowledge as low. With only 32% of participants discussing the MC with their coaches/pedagogues, communication was found to be limited. Seventy-three percent felt uncomfortable during training or competition due to their attire and recommended darker colors and more options in size and layering. The study highlights a significant gap in knowledge and communication about the MC among female athletes and coaches/pedagogues in aesthetic sports. It also recommends improving athletes` choice of attire for greater comfort and confidence.